The role of countermovement in the manifestation of explosive leg strength in vertical jumps - Stojanovic, N.; Coh, M.; Bratic, M. (Facta Universitatis: Series Physical Education and Sport, 2016)
In order to explain the role of countermovement in the manifestation of explosive strength in vertical jumps performed with and without countermovement, the difference between the components of explosive strength in those jumps was analyzed on a sample of 44 elite Serbian cadet age volleyball players. The sample of tests consisted of eight components of explosive strength manifested in vertical jumps: jump height, maximal vertical speed, duration of the concentric jump phase, maximal force, maximal relative force, the ratio between maximal force and duration of the concentric jump phase, maximal power during the concentric jump phase and the average power during the concentric jump phase. The results have shown that all the components of explosive strength are significantly greater in the case of the countermovement jump in comparison to the squat jump, except for maximal power during the concentric jump phase. The greatest differences at the numeric level are noted in terms of the force/time ratio (3415 N/s or 59.9 %), then in average power in the concentric jump phase (611 W or 38.3 %), as well as in the duration of the concentric jump phase (0.076 s or 26.7 %) and jump height (7.9 cm or 23.5 %). Nonetheless, differences are also noted in maximal relative force (0.33 N or 14.1 %) and in maximal force (215 N or 13.4 %). The least significant differences are noted in maximal vertical speed (0.09 m/s or 3.5 %). In the case of maximal power during the concentric jump phase (Pmax), no significant differences were noted. The ensuing differences are ascribed to the role of the countermovement, which produces the changes in muscle activation, and initiates the stretch-shortening cycle of the muscle, as well as the occurrence of the 'elastic potentiation' of the muscles in the case of the countermovement jump, and thus increased muscle work.